ศักยภาพการสร้างกรดและการชะละลายโลหะจากดินและถ่านหินของเหมืองแร่ลิกไนต์ - บุณฑริกา อินทะวงค์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Potentials of acid generation and metal leaching from soil and coal of lignite mine were evaluated. This study comprised two main parts. Forty two soil and coal samples collected from Mae Moh Mine were used in the first part. This included determination of total metals contaminated in the samples, by using acid digestion EPA method 3050 B, paste pH measurement, investigation of acid and metal leaching by using Synthetic Precipitation Leaching (SPLP),Waste Extraction Test (WET) and also Three-Stage Sequential Extraction procedures. For the second part, continuous acid and metal leaching from red bed clay and coal Q samples were compared. Al, As, Cd, Cr, Cu, Fe, Mn, Pb, Ni and Zn were analysed in this study. The result illustrated that Fe and Al were major metal components of all soil and coal samples. Every metal contamination in all samples were much lower than Total Threshold Limit Concentration. Therefore, all soil and coal samples were not classified as hazardous materials. Moreover, pH of most samples were neutral. Leaching potential of most metals by WET extraction fluid were higher than those of SPLP. However, all metal contents of every WET leaching solution were not exceeded Soluble Threshold Limit Concentration. Leachable Cd and Pb of most samples were in exchangeable form, while Ni, Cu and Cr were in oxidisable form. As for Zn, it was found in reducible form. For continuous leaching case, the result showed that pH of red bed clay permeate was higher than its run-off. Nevertheless, pH of coal Q permeate was lower than the run-off. Al and Fe were major metals detected in both run-off and permeate of red bed clay and also in run-off of coal Q units. However, major metal detected in permeate of coal Q unit was only Fe.